2006
DOI: 10.1037/0012-1649.42.6.1089
|View full text |Cite|
|
Sign up to set email alerts
|

Life-span development of visual working memory: When is feature binding difficult?

Abstract: We asked whether the ability to keep in working memory the binding between a visual object and its spatial location changes with development across the life span more than memory for item information. Paired arrays of colored squares were identical or differed in the color of one square and, in the latter case, the changed color was unique on that trial (item change) or was duplicated elsewhere in the array (color-location binding change). Children (8-10 and 11-12 years old) and older adults (65-85 years old) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
299
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(344 citation statements)
references
References 78 publications
(121 reference statements)
33
299
6
1
Order By: Relevance
“…Developmental trajectories in feature binding performance have previously been observed across children and into young adulthood using a range of tasks measuring within-domain visual and spatial binding (e.g., Brockmole & Logie, 2013;Cowan, Naveh-Benjamin, et al, 2006;Picard et al, 2012), verbal binding within sentences (Alloway et al, 2004;Kapikian & Briscoe, 2012), and across-domain binding between verbal and spatial information Darling et al, 2014). The present study extends this to a different task where visual and auditory-verbal materials were to be bound and held in working memory over short intervals.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Developmental trajectories in feature binding performance have previously been observed across children and into young adulthood using a range of tasks measuring within-domain visual and spatial binding (e.g., Brockmole & Logie, 2013;Cowan, Naveh-Benjamin, et al, 2006;Picard et al, 2012), verbal binding within sentences (Alloway et al, 2004;Kapikian & Briscoe, 2012), and across-domain binding between verbal and spatial information Darling et al, 2014). The present study extends this to a different task where visual and auditory-verbal materials were to be bound and held in working memory over short intervals.…”
Section: Discussionsupporting
confidence: 64%
“…In a large-scale online study of visual memory, Brockmole and Logie (2013) found that binding between colour and shape showed a developmental trajectory from 8 years old and into adolescence, with younger children recalling a higher rate of unbound features. Other studies have administered tasks tapping binding between features and locations, and generally found developmental improvements from younger to older children, and into adulthood (e.g., Cowan, Naveh-Benjamin, Kilb, & Saults, 2006;Lorsbach & Reimer, 2005;Picard et al, 2012). In the purely verbal domain, Alloway, Gathercole, Willis, and Adams (2004) examined binding using sentence recall alongside a range of other measures, and found evidence for developmental improvements from 4 years of age.…”
mentioning
confidence: 99%
“…For instance, older adults showed poor short-term memory for item-spatial location relational binding, despite intact memory for individual features (items or locations alone) (Borg, Leroy, Favre, Laurent, & Thomas-Anterion, 2011;Cowan, Naveh-Benjamin, Kilb, & Saults, 2006;Fandakova, Sander, Werkle-Bergner, & Shing, 2014;Mitchell, Johnson, Raye, Mather, & D'Esposito, 2000;Olson et al, 2004; but see Read, Rogers, & Wilson, 2016;Rhodes, Parra, Cowan, & Logie, 2017). Age-related decrease of short-term memory for face-scene pairings was also reported 4 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The associative component depends on medial temporal functioning and refers to mechanisms that bind together different aspects of an event into a cohesive representation during the encoding, storage and retrieval of episodic memories. It is relatively mature by middle childhood (around age 6), as indicated by behavioral and neuroimaging evidence (Gogtay et al, 2004;Ofen et al, 2007;Sowell et al, 2003; but see Ghetti, DeMaster, et al, 2010;Gogtay et al, 2006), and undergoes senescent decline during adulthood and old age (Brehmer, Li, Muller, von Oertzen, & Lindenberger, 2007;Cowan, Naveh-Benjamin, Kilb, & Saults, 2006;Raz, Ghisletta, Rodrigue, Kennedy, & Lindenberger, 2010;Raz et al, 2005;Sander, Werkle-Bergner, & Lindenberger, 2011). The strategic component depends on prefrontal functioning and refers to control and organizational processes during encoding, as well as strategic search, monitoring and evaluation during retrieval.…”
mentioning
confidence: 99%